Retinal rods and cones have distinct G protein beta and gamma subunits. - Peng, Y W (1992)
Guanine nucleotide-binding proteins (G proteins) involved in transmembrane signal-transduction processes are heterotrimers composed of alpha, beta, and gamma subunits. The alpha subunit shows great diversity and is thought to confer functional specificity to a particular G protein. By contrast, the beta and gamma subunits appear much less diverse; in particular, the beta subunit is believed to have no role in G protein specificity. Using immunocytochemistry, we found distinct distribution patterns for different beta and gamma subunits in the retina. In particular, rod and cone photoreceptors, which both subserve phototransduction but differ in light-response properties, have different beta and gamma subunits in their outer segments. Thus, the G protein mediating phototransduction shows cell-specific forms of the beta and gamma subunits in addition to the alpha subunit. This surprising finding supports the hypothesis that these subunits may also contribute to functional specificity of a G protein.